Micro–macro interactions and effect of section thickness of hpdc AZ91 Mg alloy - Leo Prakash (Journal of Alloys and Compounds, 2008)
This work is aimed to conclude the effect of section thickness of a high pressure die cast (hpdc) Mg alloy on the tensile properties as ambiguous conclusions are presented in the literature. Tensile tests were performed on as-cast hpdc AZ91 alloy and the effect of section thickness on the tensile properties such as yield strength (YS), ultimate tensile strength (UTS), ductility and fracture strain (FS) are explained. Additionally, explanation on the microfailure mode of the material is presented to explain the influence of different microfeatures on the failure process. The average size, area fraction and clustering tendency of pores and Mg17Al12 (β) particles as well as average grain size are quantified and their effects on section thickness are obtained. The results confirm that the UTS, YS, ductility and FS are mainly influenced by the area fraction, size distribution and spatial arrangement of pores and phases.